2007
DOI: 10.1177/10105395070190010901
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Regimens and Glycemic Control of Patients with Type 2 Diabetes Attending a Tertiary Hospital Clinic

Abstract: This cross-sectional study is aimed to measure the prevalence of patient adherence to treatment regimens and factors affecting glycemic control among Type 2 diabetes patients. 243 diabetes patients seeking care at a tertiary hospital diabetic clinic in Bangkok were interviewed. HbA1c was used as an index of glycemic control. The proportions of cases with good adherence to physical exercise and diet regimen were 31.7 and 54.3%, respectively. About 46.5% reported receiving good social support for diabetes from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 19 publications
(14 reference statements)
8
22
3
3
Order By: Relevance
“…Adherence to dietary restrictions and diet plans was also related to improved diabetes control. Similar findings were reported by Howteerakul et al [13] who reported that adherence to diet control and exercise were significantly associated with glycemic control. Another study by Matsushita et al [25] found that patients who were able to estimate their energy intake reasonably well had better glycemic control.…”
Section: Discussionsupporting
confidence: 84%
“…Adherence to dietary restrictions and diet plans was also related to improved diabetes control. Similar findings were reported by Howteerakul et al [13] who reported that adherence to diet control and exercise were significantly associated with glycemic control. Another study by Matsushita et al [25] found that patients who were able to estimate their energy intake reasonably well had better glycemic control.…”
Section: Discussionsupporting
confidence: 84%
“…These findings were consistent with studies performed in other parts of the world [18,[25][26][27]. In our study population, outdoor walking was the most commonly reported physical activity, and is consistent with previous reports [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Five studies used more than one measure to assess social support [42,43,45,46,48]. Eight studies assessed support specific to diabetes care [27,30,32,35,36,40,44,46] and two studies used measures of social support specific to chronic disease [26,29]. We did not separate results into functional and structural support due to heterogeneity in measurements of social support.…”
Section: Resultsmentioning
confidence: 90%
“…Measures of social support were varied, with little overlap across studies. The most frequently used measures were multidimensional assessments of social support (measures that assessed more than one component of social support) (n = 16) [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Of these, 13 studies generated a composite measure of social support and 3 studies separated analysis by social support type [37][38][39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation